Digitizing Pre-1978 Dissertations at Binghamton University Libraries - Rushton, Erin E; Holton, Caitlin; McDermott, Jamey (Library resources & technical services, 2025)
In 2023, Binghamton University Libraries initiated a project to digitize its pre-1978 dissertationsand make them available in its institutional repository. This Communication on Practice provides anoverview of the key decisions made before embarking on the project, the workflow, and the challenges encountered. We drew upon the experiences and lessons learned from other institutions to guide our process, and hope this paper will serve as a resource for those considering similar projects at their institutions.